Understanding Multiple Ecosystem Services of Urban Agriculture Across Scales - Jiangxiao Qiu; Hui Zhao (EDIS)
Urban agriculture has gained momentum in global research and policy, and is proposed to combat challenges such as food insecurity, climate change, and social inequality. Here we provide an overview of ecosystem services urban agriculture provides. We found a general agreement that urban agriculture could deliver: (1) food production; (2) microclimate and air quality regulation; (3) stormwater retention; (4) waste management and nutrient recycling; (5) biodiversity conservation; (6) climate regulation and mitigation; (7) energy conservation; and (8) social-cultural values. But quantitative evidence is scarce for many ecosystem services, especially those that are intangible. Urban agriculture could be integral to green infrastructure, included in urban and regional planning, but consideration should also be given to types of urban agriculture, the role of technology and management practices, and potential tradeoffs, risks, and disservices.